Menganalisis Pengaruh Cadangan Kerugian Penurunan Nilai (CKPN), Dana Pihak Ketiga (DPK), dan Non-Performing Financing (NPF) Terhadap Profitabilitas Perbankan Syariah di Indonesia - Pani Akhiruddin Siregar; Suginam Suginam; Nur'ain Harahap; Hastuti Olivia (Ekonomi, Keuangan, Investasi dan Syariah (EKUITAS), 2023)
This research aims to analyze the effect of CKPN, DPK, and NPF on the profitability of Sharia Banking in Indonesia. The population in this research was sourced from the Financial Ratios of Sharia Commercial Bank and Business Activities of Sharia Commercial Bank through the publication of Sharia Indonesia Banking Statistic, Financial Services Authority (SPS OJK). The secondary data is taken on a monthly time series from January 2019 to June 2023. At least, the data that can be further analyzed is 65 data. Sampling techniques non-probability sampling by means of purposive sampling. The results of the research are as follows: (1) Judging from the results of the R2 accuracy test that the estimation model shows an R2 value of 0,41. That is, the R2 value obtained represents the coefficient of determination. This means that 41% of the dependent variable variation is able to be explained by the independent variable in this model. The remaining 59% is explained by other causes that are not included in the model; (2) Judging from the results of the F test that the regression model on the independent variable simultaneously effect the dependent variable so that the regression model of the independent variable can be used to predict the dependent variable; and (3) Judging from the results of the t test that this research produced output according to the hypothesis where CKPN, DPK, and NPF had an effect and were significant on ROA.